Autocad civil 3d 2016 essentials : autodesk official press - Chappell, Eric (Sybex, 2015)
Start designing today with this hands-on beginner's guide to AutoCAD Civil 3D 2016 AutoCAD Civil 3D 2016Essentials gets you quickly up to speed with the features and functions of this industry-leading civil engineering software. This full-color guide features approachable, hands-on exercises and additional task-based tutorials that help you quickly become productive as you master the fundamental aspects of AutoCAD Civil 3D design. Each chapter opens with a quick discussion of concepts and learning goals, and then briskly moves into tutorial mode with screen shots that illustrate each step of the process. The emphasis is on skills rather than tools, and the clear delineation between "why" and "how" makes this guide ideal for quick reference. The companion website provides starting and ending files for each exercise, so you can jump in at any point and compare your work with the pros. Centered around the real-world task of designing a residential subdivision, these exercises get you up to speed with the program's functionality, while also providing the only Autodesk-endorsed preparation for the AutoCAD Civil 3D certification exam.-Master the AutoCAD Civil 3D 2016interface and basic tasks -Model terrain using imported field survey data -Analyze boundaries, pipe networks, surfaces, and terrain -Estimate quantities and create construction documentation If you're ready to acquire this must-have skillset, AutoCAD Civil 3D 2016Essentials will get you up to speed quickly and easily.